The Spirituality of Hryhorii Skovoroda’s Work in Taras Zakydalsky’s Research - Alchuk, M. P; Pavlyshyn, A. D (Anthropological Measurements of Philosophical Research, 2022)
The purpose of the article is to introduce into scientific circulation works by Ukrainian scholar Taras Zakydalsky on the philosophy of Hryhorii Skovoroda. Taras Zakydalsky is a representative of the Ukrainian diaspora, philosopher, and member of Canadian NTSh (Shevchenko Scientific Society of Canada). Theoretical basis. We consider the uniqueness of H. Skovoroda’s philosophy, which stimulates not only intellectually but also spiritually enlightens the reader. The reasons for the complex perception and interpretation of Hryhorii Skovoroda’s philosophy are highlighted. We have verified the main methods of its interpretation given in the works by Dmytro Chyzhevskyi. The influence of philosophical thought of thinkers of Antiquity and the Middle Ages: Aristotle, Epicurus, the Church Fathers, and Tertullian has been studied. We have comprehended H. Skovoroda’s interpretation of the Bible as a two-layer existence, the symbolic world that makes the foundation of his philosophy. The peculiarity of the thinker’s division of the heart into "internal" and "external" is analyzed. Hryhorii Skovoroda’s position on the Good and the evil is stated. The Good is identified with God, and the evil – with the real world, the man can choose between the two. Much attention is paid to the understanding of man as a microcosm – rational thinking, and thought is the fundamental cause of human activity, which generates all existence. Hryhorii Skovoroda’s philosophy of metaphysics as the existence of three worlds is highlighted: the first is the macrocosm (the whole surrounding world), the second is the microcosm (the man), and the third is the symbolic world (the Bible). "Monodualism" as a characteristic feature of H. Skovoroda’s work is analyzed. We have highlighted H. Skovoroda’s attitude to the transcendence of God, which is not separated from the world but is present in it directly. The understanding of faith as a forced act of self-love is analyzed because by loving ourselves we love God. The criteria for true and false faith have been clarified. The significance of H. Skovoroda’s aphorism that what is necessary is useful, and not useful is unnecessary is considered. Examples of ethical principles in H. Skovoroda’s philosophy are considered. Peculiarities of the concept HAPPINESS are revealed. This concept is a universal means of existence of the Good, its source is gratitude to God. Originality of the article is in the systematic presentation of the philosophy of the heart by Hryhorii Skovoroda and the analysis of the integrity of the "inner man", the true meaning of life as interpreted by Taras Zakydalsky. Conclusions summarize the "anthropological pragmatism" of the philosopher, whose main idea is to apply practical skills for the benefit of society.